Prevalence and outcomes of trans-radial access for percutaneous coronary intervention in contemporary practise. (15th October 2016) - Asrar ul Haq, Muhammad; Tsay, It Meng; Dinh, Diem T.; Brennan, Angela; Clark, David; Cox, Nicholas; Harper, Richard; Nadurata, Voltaire; Andrianopoulos, Nick; Reid, Christopher; Duffy, Stephen J.; Lefkovits, Jeffrey; et al.
Abstract: Background: Trans -radial access for percutaneous coronary intervention (PCI) has been associated with lower vascular complication rates and improved outcomes. We assessed the current uptake of trans -radial PCI in Victoria, Australia, and evaluated if patients were selected according to baseline bleeding risk in contemporary clinical practise, and compared selected clinical outcomes. Methods: PCI data of all patients between 1st January 2013 and 31st December 2014 were analysed using The Victorian Cardiac Outcomes Registry (VCOR). Propensity-matched analysis was performed to compare the clinical outcomes. Results: 11, 711 procedures were analysed. The femoral route was the predominant access site (66%). Patients undergoing trans -radial access PCI were younger (63.9 ± 11.6 vs. 67.2 ± 11.8; p < 0.001), had a higher BMI (28.9 ± 5.5 vs. 28.5 ± 5.2; p < 0.001), more likely to be male (80.0 vs. 74.9%; p < 0.001), less likely to have presented with cardiogenic shock (0.9 vs. 2.8%; p < 0.001) or have the following comorbidities: diabetes (19.8 vs. 23.1%; p < 0.001), peripheral vascular disease (2.9 vs. 4.3%; p = 0.005) or renal impairment (13.6 vs. 22.1%; p < 0.001). The radial group had less bleeding events (3.2 vs. 4.6%; p < 0.001) and shorter hospital length of stay (3.1 ± 4.7 vs. 3.3 ± 3.9; p = 0.006). There was no significant difference in mortality (1.0 vs. 1.4%; p = 0.095). Conclusions: Trans -femoral approach remains the dominant access site for PCI in Victoria. The choice of route does not appear to be selected by consideration of bleeding risk. The radial route is associated with improved clinical outcomes of reduced bleeding and length of stay consistent with previous findings, and this supports the efficacy and safety of trans -radial PCI in real-world clinical practise.